Крестный отец: роман / Марио Пьюзо ; [перевод с английского М. Кан] - Пьюзо Марио (Pocket book, 2013)
Экземпляры: ф.4 (20151126) / Инвентарный номер: 059942 / Цена: 70.00 / Авт.знак: П 96 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)